Specification, Projection, And Investment In Islam - Siti Ardila Siregar; Nisa Andriani Saragih; Zati Hulwani; Wella Triani (Proceeding International Seminar of Islamic Studies, 2019)
Some of us are not aware of the importance of investment and do not need to be done. Most of them prefer to save their money in a bank or have a deposit in a bank. They worry that the results obtained are not what they want and they are looking for sure and safe. In fact, if we make the right investment, we will get very satisfying results. There are so many reasons why we need to invest including avoiding inflation, earning huge profits, for the future and many more. But in Islam investment it self is basically an active Islamic economic activity. Because in Islam the property has a limit or if it reaches the threshold of the treasure there is zakat, or at least the property is offered. As the Qur'an recommends "Every piece of your treasure there is also a part of other people who are entitled to receive it". Investment from a social perspective is based more on helping people who have capital but cannot manage and run their businesses. And in the concept of Islamic investment based on the value of monotheism, fair wal ihsan, endeavor, and obligations. This study aims to look at the effect of investment in the future economy and analyze some of the points in investment. This study examines the mechanism of investment and the effect of investment on the future economy. By using comparative theories whether investment has a positive and significant effect on the Indonesian economy.